The Examination of Communication Skills and Self-Efficacy of Coaches - Hayri Demir; Selçuk Buğdaycı (Türk Spor ve Egzersiz Dergisi)
This study was conducted to examine the communication skills and self-efficacy levels of individuals working as coaches. The population of this study, which was conducted using a descriptive research model, consisted of coaches working actively in Turkey, while the sample group consisted of a total of 697 coaches, 203 women and 494 men, on a voluntary basis. The data were obtained by using "Personal Information Form", "General Self-Efficacy Scale" and "Communication Skills Assessment Scale". Independent Samples t test, One Way ANOVA test, Person correlation analysis were used to reach statistical results. It was concluded that the self-efficacy score averages of the coaches participating in the study were higher than the averages of communication skills sub-dimensions. While there was a statistical difference between the education level of the male coaches participating in the study and the communication principles and basic skills sub-dimensions of communication skills, no difference was found in other sub-dimensions. While there was no statistical difference in the communication skills sub-dimensions and the education level of female coaches, a significant difference was found in general self-efficacy scores. Significant differences were found in the coaching levels of male coaches participating in the study and in the sub-dimension of general self-efficacy and communication. In addition, significant differences were found in the coaching levels of female coaches and in the sub-dimensions of self-expression, active listening and non-verbal communication and willingness to communicate. As a result, there is a parallelism between the self-efficacy and communication skills of the coaches participating in the study. In other words, it can be said that as the competence of male and female coaches in their jobs increases, their communication skills also increase.